Decision Support System To Determine The Best Tax Payer Nominee At Regional Government Using Saw & Ahp - Wahyu Aziz Prastiyo; R. Dimas Adityo; Syariful Alim (JEECS (Journal of Electrical Engineering and Computer Sciences), 2022)
Tax, as generally known, are important aspect for Indonesia country sustainability. Taxpayer compliance is a conditionwhere the taxpayer has completed all of their tax obligations and get their tax rights. These compliance are identifiedwhen they send back SPT and their compliance of paying tax debts. Decision support system is a part of computerizedinformation system. AHP-SAW is one kind of a method which developed by combining weight and comparisonbetween criteria to determine the best alternative. Using the method, this research will help the tax office to choosewhich hotel and restaurant are eligible to get the best criteria in tax compliance. Based on the test result, for hotel,accuracy obtained is 78.6% on average, where Hotel Wijaya 1 always get the first rank. For restaurant, the accuracyobtained is 84.7%, where RM Ramio always get the first rank. Business entity criteria has big impact on rankingprocess where in a 100% accuracy test, this criteria got bigger value than other criteria.